Fluconazole-Induced Ploidy Change in Cryptococcus neoformans Results from the Uncoupling of Cell Growth and Nuclear Division - Sophie Altamirano (American Society for Microbiology, 2017)
ABSTRACT Cryptococcus neoformans is a pathogenic yeast that causes lethal cryptococcal meningitis in immunocompromised patients. One of the challenges in treating cryptococcosis is the development of resistance to azole antifungals. Previous studies linked azole resistance to elevated numbers of copies of critical resistance genes in aneuploid cells. However, how aneuploidy is formed in the presence of azole drugs remains unclear. This study showed that treatment with inhibitory concentrations of an azole drug, fluconazole (FLC), resulted in a significant population of cells with increased DNA content, through the following defects: inhibition of budding, premature mitosis, and inhibition of cytokinesis followed by replication in the mother cell. Inhibition of and/or a delay in cytokinesis led to the formation of cells with two or more daughter cells attached (multimeric cells). To investigate which part of cytokinesis fails in the presence of FLC, the dynamics of the actomyosin ring (AMR), septins, and Cts1, a protein involved in cell separation, were analyzed with time-lapse microscopy. Following the constriction of the AMR, septins assembled and the septum was formed between the mother and daughter cells. However, final degradation of the septum was affected. Enlarged cells with aberrant morphology, including multimeric cells, exhibited an increased potential to proliferate in the presence of FLC. These findings suggest that pleiotropic effects of FLC on growth and mitotic division lead to an increase in DNA content, resulting in cells less sensitive to the drug. Cells with increased DNA content continue to proliferate and therefore increase the chance of forming resistant populations. IMPORTANCE Azoles are antifungals that are widely utilized due to relatively low toxicity and cost of treatment. One of their drawbacks, however, is that azoles are primarily cytostatic, leaving fungal cells capable of developing drug resistance. The human pathogen Cryptococcus neoformans acquires resistance to the azole drug fluconazole (FLC) through the development of aneuploidy, leading to elevated expression of key resistance genes, a mechanism that is also common for Candida albicans (K. J. Kwon-Chung and Y. C. Chang, PLoS Pathog 8:e1003022, 2012, https://doi.org/10.1371/journal.ppat.1003022 ; J. Morschhäuser, J Microbiol 54:192–201, 2016, https://doi.org/10.1007/s12275-016-5628-4 ). However, the exact ways in which FLC contributes to increased resistance in either of these important fungal pathogens remain unclear. Here we found that FLC treatment leads to an increase in DNA content in C. neoformans through multiple mechanisms, potentially increasing the size of a pool of cells from which aneuploids with increased resistance are selected. This study demonstrated the importance of FLC’s inhibitory effects on growth and cytokinesis in the generation of cell populations with decreased sensitivity to the drug.